PELUANG DAN TANTANGAN INDONESIA MENGHADAPI PERTUMBUHAN EKONOMI CHINA INDIA (CHINDIA) - ragimun, Ragimun (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2009)
The economic growths of China and India which are rising surprisingly on the last decade have showed asthe new economic power in the world. At the same time, at the different regions, those have stagnant of theirgrowth, China and India demonstrate high growth. This gives an opportunity to many other countries whichhave economic partnership to them, especially Indonesia. There are so many goods come from China and Indiathat have filled out to Indonesia and some other countries in Asia. From Indonesia’s perspective, the China and India growth have brought some opportunities with theirsupply of raw materials and supporting goods for domestic industries. On the other hand, Indonesia is facing abig threat regarding the goods and products from China and India. The possible way to overcome this matter isto maintain and improve the quality of our products so they could compete with them.Keywords: Chindia, opportunity , Indonesia’s growth